Meat quality and muscle proteome of commercial broiler chickens subjected to pre slaughter electrical stunning and gas killing - Md Saad, Salwani (2014)
Stunning prior to slaughter of animal is desired for i) animal welfare ii) high throughput of processing, and iii) meat quality. However, different stunning procedures may alter the biochemical changes thus the outcome on meat quality differently. This study was conducted to determine the effects of electrical stunning and gas killing prior to slaughter on meat quality and skeletal muscle proteome of commercial broiler chickens. The meat quality parameters examined are pH values, cooking loss, drip loss, tenderness and colour values (L*, a*, b*). Two separate experiments were conducted separately. In Experiment 1, 40 commercial broiler chickens (2.60±0.2 kg) were randomly assigned to electrical stunning (constant voltage of 30 V, 0.2 A, 50 Hz for 5s) and control (without stunning). Immediately after stunning, the broilers were subjected to manual neck cut using a sharp knife. In Experiment 2, 40 broiler chickens (2.60±0.2 kg) were randomly assigned to gas killing (40% carbon dioxide, 30% oxygen and 30 % nitrogen) and control (without prior gas killing), following which, the broilers were slaughtered immediately. Pectoralis major muscles were sampled for muscle proteome and the remaining were assigned for muscle pH, tenderness, cooking loss, drip loss and colour assessments at 0, 4 and 24 h postmortem. Muscle samples of the electrically stunned broilers presented lower (p<0.05) cooking loss and lightness values (L*). The gas killing had resulted in lower pH values (p<0.05), lower shear force values (p<0.05), higher cooking loss (p<0.05), higher drip loss (p<0.05) and lower lightness values (p<0.05). The muscle proteome revealed expression changes (p<0.05) of several proteins in both treatments. In electrical stunning, beta enolase, pyruvate kinase muscle isozyme and glycogen phosphorylase were expressed lower as compared to the control. On the contrary, gas killing treatment has significantly increased the expressions of beta enolase and pyruvate kinase, and reduced the expression of creatine kinase. In conclusion, electrical stunning had reduced the glycogen metabolism with improved meat quality. Meanwhile, the gas killing procedure had significantly elevated the glycolysis rate which resulted with poorer meat quality. It seems that the gas killing is more detrimental on meat quality as compared to electrical stunning.